2015
DOI: 10.1039/c5en00057b
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of 12 metal-based nanoparticles to algae, bacteria and protozoa

Abstract: The use of metal based nanoparticles (NPs) is increasing which leads to their release in water bodies via various waste streams and warrants risk assessment. Consistent biological effect data on NPs for environmentally relevant test species that are accompanied by thorough characterization of NPs are scarce but indispensable for understanding possible risks of NPs. We composed and tested a library of 12 metal-based nanoparticles () using alga Pseudokirchneriella subcapitata, three bacterial species (Vibrio fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(132 citation statements)
references
References 71 publications
11
120
1
Order By: Relevance
“…23, 46, 8183 The biological response was then delineated by engineering ZnO NPs via Fe doping. 46, 8486 In the present investigation, the decreased toxicity at cellular level and the reduced hatching interference in the zebrafish embryo (safe-by-design strategy) is established for Fe doped CuO NPs (Figure 12).…”
Section: Discussionmentioning
confidence: 99%
“…23, 46, 8183 The biological response was then delineated by engineering ZnO NPs via Fe doping. 46, 8486 In the present investigation, the decreased toxicity at cellular level and the reduced hatching interference in the zebrafish embryo (safe-by-design strategy) is established for Fe doped CuO NPs (Figure 12).…”
Section: Discussionmentioning
confidence: 99%
“…C). The effects of agglomerated nanoparticles within some protozoa have been reported: Not all types of nanoparticle caused acute toxicity in the protozoa Tetrahymena thermophile (24 H EC 50 >1,000 mg/mL) , and nontoxic nanotitanium dioxide (nTiO2) could agglomerate in Paramecium .…”
Section: Resultsmentioning
confidence: 99%
“…MOx NPs agglomeration was also characterized by a sedimentation assay (Aruoja et al 2015;Hartmann et al 2013;OECD 2017). For this purpose, NPs were suspended in YEP or MES buffer, at a final concentration of 100 mg/L, and agitated at 150 rpm for 24 h, at 30°C, in the absence of yeast cells.…”
Section: Characterization Of Nps Suspensions In Different Mediamentioning
confidence: 99%
“…Studies in soils showed that Al 2 O 3 , SiO 2 and SnO 2 NPs had an impact in bacterial and in fungal community (Chai et al 2015;Chavez-Calderon et al 2016;McGee et al 2017). Other studies showed that Al 2 O 3 , Mn 3 O 4 and SiO 2 NPs caused growth inhibition of bacteria (Escherichia coli and Staphylococcus aureus), algae (Pseudokirchneriella subcapitata) and protozoa (Tetrahymena thermophila and Paramecium multimicronucleatum) and bioluminescence reduction of the bacterium Vibrio fischeri (Aruoja et al 2015;Li et al 2012). SnO 2 NPs caused a reduction of cell viability and provoked the damage of cell membrane in the bacteria E. coli and Bacillus subtilis (Chavez-Calderon et al 2016).…”
Section: Introductionmentioning
confidence: 99%